Pelatihan Debat Bahasa Inggris Berbasis British Parliamentary Debate System di Program Studi Pendidikan Bahasa Inggris - Nizar Saputra; Surya Asra; Fadlia Fadlia; Allif Syahputra Bania; Tarwiyah Tarwiyah (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
With the increasing interest and participation of students in debating activities at both the campus and national levels, debates are considered as an activity that provides broad benefits for the development of students' critical thinking, analytical, and communication skills. However, to compete effectively in the increasingly competitive debate competitions, students need a deep understanding of the debate system commonly used in competitions, such as the National University Debate Championship (NUDC).This community service article focuses on English debate training based on the British Parliamentary Debate System for students at English Language Education Study Program at Samudra University. This service program aims to prepare students to participate in regional and national debate competitions. The implementation of the training program includes a variety of effective methods, including theoretical lectures, debate simulations, group discussions, provision of reading materials, and evaluation of feedback. The results obtained from this program include improving students' English language skills, understanding of the British Parliamentary Debate System debate system, developing critical and analytical thinking skills, increasing self-confidence and communication skills, and readiness to take part in local and national debate competitions. The results of this community service not only benefit students, but also contribute to the development and reputation of English Education Study Program at Samudra University as a whole.